Strategic Analysis of Urban Fire Management Systems - Abdul Hakim; Iman Basriman; Ninin Gusdini (Journal of Social Research, 2023)
A fire is a condition of a building, such as a house, factory, market, or building, burning uncontrollably, causing casualties. Fire is one of the disasters caused by non-natural factors. The purpose of this study is to analyze internal and external environmental factors in the prevention of fire management. As well as designing a strategy formulation for fire prevention. the method used in this study is a SWOT analysis using the QSPM (Quantitative Strategy Planning Matrix). The number of respondents in this study was three people. The results of this study are based on interviews with the fire service which resulted in factors influencing the occurrence of internal and External fires during the fire suppression strategy. The most influential internal factor in terms of strength is establishing an RW-level early handling officer providing counseling to the community. Already has a lot of fleet facilities. Lack of training in new firefighters. External factors in Fire prevention among them. Providing external training to fire officers in the agency/community while in terms of threats, namely weak cooperation with electricity, and water providers. Strategies that can improve at the time of fire prevention in the future. Increase the capacity of building fire prevention to the community and agencies and residents maximize early fire prevention can be done so that the fire is extinguished immediately.